CONSORT the effect of a bolus dose of dexmedetomidine on postoperative pain, agitation, and quality of recovery after laparoscopic cholecystectomy. Issue 3 (22nd January 2021) - Choi, Jung Ju; Kim, Kyungmi; Park, Hee Yeon; Chang, Young Jin; Lee, Kyung Cheon; Kim, Kwan Yeong; Kwak, Hyun Jeong
Abstract: Background: The perioperative administration of dexmedetomidine may improve the quality of recovery (QoR) after major abdominal and spinal surgeries. We evaluated the effect of an intraoperative bolus of dexmedetomidine on postoperative pain, emergence agitation, and the QoR after laparoscopic cholecystectomy. Methods: Patients undergoing elective laparoscopic cholecystectomy were randomized to receive dexmedetomidine 0.5 μg/kg 5 minutes after anesthesia induction (dexmedetomidine group, n = 45) or normal saline (control group, n = 45). The primary outcome was the QoR at the first postoperative day using a 40-item scoring system (QoR-40). Secondary outcomes included intraoperative hemodynamic parameters, postoperative agitation, pain, and nausea and vomiting. Results: The heart rate and the mean blood pressure were significantly lower in the dexmedetomidine group than in the control group ( P  < .001 and .007, respectively). During extubation, emergence agitation was significantly lower in the dexmedetomidine group than in the control group (23% vs 64%, P  < .001). The median pain scores in the post-anesthetic care unit were significantly lower in the dexmedetomidine group than in the control group (4 [2–7] vs 5 [4–7], P  = .034). The incidence of postoperative agitation, pain, and nausea and vomiting was not different between the groups. On the first postoperative day, recovery profile was similar between the groups. However, the scores on the emotional state and physical comfort dimensions were significantly higher in the dexmedetomidine group than in the control group ( P  = .038 and .040, respectively). Conclusions: A bolus dose of dexmedetomidine after anesthesia induction may improve intraoperative hemodynamics, emergence agitation, and immediate postoperative analgesia. However, it does not affect overall QoR-40 score after laparoscopic cholecystectomy.